Bentuk dan Makna Pertunjukan Tari Renteng di Desa Saren, Nusa Penida, Klungkung, Bali - Ni Made Ruastiti; Anak Agung Indrawan; Ketut Sariada (Pusat Kajian Bali Universitas Udayana, 2021)
This article discusses the meaning of Renteng Dance in the Saren Village of Nusa Penida. In Bali, there are many ceremonial dances, but recently many people have created ceremonial dances inspired by the Renteng Dance. This study focuses on the forms and meanings of the Renteng Dance shown in Saren Village. Data collected through observation, documentation study, and interviews with informants were analyzed descriptively using aesthetic theory and reception. It can be concluded that the people of Saren Village performed the Renteng Dance in the form of tari lepas which is a dance performance without stories. This can be seen from the presentation, choreography, and the music accompanying the performance. Renteng dance is accompanied by Balinese gamelan Balaganjur music with a specific movement dance performance structure. Saren community members support this dance because it has meaning as an expression of faith, social concern, and the interest in ecological preservation.